Public expectation, pressure, and avoiding-the-choke: A case study from elite sport - Hodge, K.; Smith, W. (The Sport Psychologist, 2014)
This case study focused on pressure, stereotype threat, choking, and the coping experiences of the New Zealand All Blacks rugby team during the period from 2004-2011 leading into their success at the 2011 Rugby World Cup (RWC). Employing a narrative approach this case study examined public expectation, pressure, and coach-led coping strategies designed to "avoid the choke" by the All Blacks team. An in-depth interview was completed with one of the All Blacks` coaches and analyzed via collaborative thematic analysis (Riessman, 2008). In addition multiple secondary data sources (e.g., coach & player autobiographies; media interviews) were analyzed via holistic-content analysis (Lieblich et al., 1998). Collectively these analyses revealed five key themes: public expectation and pressure, learning from 2007 RWC, coping with RWC pressure, decision-making under pressure, and avoiding the choke. Practical recommendations are offered for team sport coaches with respect to coping with pressure and avoiding choking.